The origins, development and significance of the circuit in Wesleyan and primitive Methodism in England 1740-1914 - Pocock, Christine Margaret (2015)
This thesis is a contribution to the organisational history of Methodism. It seeks to investigate and record the origins, development and significance of the circuit in the connexional structure of Methodism. This in order to rectify what is an omission in Methodist histories and to inform future reflection on organisation. The field of research is Wesleyan and Primitive Methodism in England from c. 1740 to 1914.